Comparison of the experimental and numerical results of coaxial-type and U-type deep-buried pipes' heat transfer performances. (July 2023) - Li, Chao; Jiang, Chao; Guan, Yanling; Chen, Hao; Yang, Ruitao; Wan, Rong; Shen, Lu
Abstract: The ground heat exchanger (GHE) is one of the main forms of geothermal energy utilization in middle-deep strata and typically includes coaxial-type deep-buried GHE (C-DGHE) and U-type deep-buried GHE (U-DGHE). This study compares the heat transfer characteristics of C-DGHE and U-DGHE. A field experiment was carried out on C-DGHE and U-DGHE at 2539 and 2781 m depths, respectively, in a housing estate in Xi'an. Simultaneously, the full-scale numerical models of both C-DGHE and U-DGHE at 2781 m were established based on the field logging data. A short-term experiment (72 h) and a long-term heat transfer simulation (five heating periods) serve to comprehensively compare the heat transfer performances of the two deep-buried pipe types. Results demonstrate that the heat transfer amount per unit meter of C-DGHE and U-DGHE were 132.18–145.91 W/m and 111.15–140.76 W/m respectively in this study, which means C-DGHE is superior to U-DGHE under similar boundary conditions when only heat transfer in buried pipes is considered. However, when heat transfer in buried pipes and water pump power consumption are considered simultaneously, a critical G ( G C was ∼8.63 kg/s in this study) makes the comprehensive heat transfer performance of U-DGHE better than that of C-DGHE.